Lectotypification of Ischaemum molle (Andropogoneae, Poaceae) - Tiwari, Arjun Prasad; Gavade, Sandip; Lekhak, Manoj (Phytotaxa, 2016)
The genus Ischaemum Linnaeus (1753: 1049) was established with two species, viz. I. muticum Linnaeus (1753: 1049) and I. aristatum Linnaeus (1753: 1049). Presently, it comprises c. 71 species distributed in warm and tropical regions of the world (Mabberley 2008). In India, the genus is represented by about 56 species and six infraspecific taxa, of which 43 are endemic and confined to Peninsular India, including Maharashtra and North-East India (Shrivastava & Nair 2010).